2020
DOI: 10.1386/hosp_00019_1
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z and hospitality careers

Abstract: This article explores youth career decision-making at a time of ongoing concerns surrounding the supply of labour to the hospitality industry. This article is unique in its combination of attitudes of Generation Z with a pre-university-aged sample combined with employer views. A survey of 245 youth provided insights into work values and attitudes towards hospitality careers, which was complemented by interviews with nine hospitality employers. Findings indicate only a small percentage of youth consider hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Gray and Farrell (2020) found that, even in Irish restaurants, apprentice chefs are severely stigmatized, posing a major recruitment challenge. Walmsley et al (2020) studied general attitudes toward social status, image and self-esteem among hospitality employees and found that a large proportion of prospective employees (students) perceived hotel positions as low status and not socially respectable. Therefore, existing research has explored the impact of occupational stigma in empirical studies involving psychological variables such as occupational commitment and self-esteem; however, some point to the positive impact of occupational stigma, such as Durand and Vergne (2015) and Helms and Patterson (2014), who suggest that practitioners of stigmatized occupations (e.g.…”
Section: Literature Review and Theoretical Framework 21 Studies On Oc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gray and Farrell (2020) found that, even in Irish restaurants, apprentice chefs are severely stigmatized, posing a major recruitment challenge. Walmsley et al (2020) studied general attitudes toward social status, image and self-esteem among hospitality employees and found that a large proportion of prospective employees (students) perceived hotel positions as low status and not socially respectable. Therefore, existing research has explored the impact of occupational stigma in empirical studies involving psychological variables such as occupational commitment and self-esteem; however, some point to the positive impact of occupational stigma, such as Durand and Vergne (2015) and Helms and Patterson (2014), who suggest that practitioners of stigmatized occupations (e.g.…”
Section: Literature Review and Theoretical Framework 21 Studies On Oc...mentioning
confidence: 99%
“…Research perspectives have included social identity (Link and Phelan, 2001), self-validation (Shantz and Booth, 2014) and resource conservation (Hobfoll, 2001a). From the perspective of the mechanism driving, existing studies have explored the mechanism of occupational stigma (Kusluvan et al , 2022), the empirical study of occupational stigma and commitment (Jerez-Jerez and Melewar, 2020; Shigihara, 2018), occupational stigma and self-esteem (Walmsley et al , 2020) and occupational stigma effects and countermeasures (Li et al , 2020). Though the extant research has discussed occupational stigma in various relevant industries, the hotel industry, which has been greatly affected by the COVID-19, it has not been sufficiently addressed, especially regarding the mechanism of the action and resolution of occupational stigma across different job types in the hotel industry.…”
Section: Introductionmentioning
confidence: 99%
“…When searching for new employees from Generation Z, it is necessary to understand this generation's work values and how they make decisions when choosing a job. Family plays a significant role when Generation Z decides on their future career (Goh & Lee 2018;Walmsley et al 2020).…”
Section: Theoretical Background 21 Generation Zmentioning
confidence: 99%
“…Job satisfaction and career prospects appeared to be more important than salary range (Goh & Lee 2018), although salary becomes more important depending on the cost of living in specific regions (Walmsley et al 2020). Nevertheless, job satisfaction includes knowledge of company values, vision, and strategic goals, as well as instant feedback or work-life balance (Chillakuri 2020).…”
Section: Theoretical Background 21 Generation Zmentioning
confidence: 99%
“…This stark contrast suggests that research on understanding applicant attitudes to recruitment efforts from the hospitality literature is lagging behind. In addition, considering the high rates of turnover and vulnerability of the industry to change, examining the factors affecting applicant attitudes and subsequent behaviors is crucial in maintaining and recruiting a viable workforce in the present and into the future of hospitality (Walmsley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%